Business-focused IT and service excellence - Miller, David (United Kingdom : BCS Publishing, 2008)
A revolutionary, new service excellence model that creates more accurate alignment between service providers and business customers. IT remains crucial to the on-going success of most businesses, and David Miller's new model helps service providers gain a clear understanding of the businesses they seek to serve.
1 Service -- 2 Service Excellence -- 3 The Service Engine and the Total Business Experience -- 4 Bringing it all Together -- 5 A New Maturity Model -- 6 Summary
Includes bibliographical references.
Keywords: BUSINESS AND ECONOMICS -- INFRASTRUCTURE